2022
DOI: 10.21608/aijpms.2022.117220.1108
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoperazine-Loaded Leciplexes as Potential Nasal Delivery Systems for treatment of depression

Abstract: Trifluoperaizne (TFP) is an antipsychotic medication with limited oral bioavailability due to extensive first-pass metabolism; consequently, the goal of this project was to develop Leciplex nanoparticles to improve the bioavailability of TFP and to prolong its nasal residence time for treatment of the depression. Leciplex NPs were prepared using negatively charged phospholipid, cationic surfactant and biocompatible solvent and optimized using the 21 31 full factorial statistical design using various surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Although both QAS molecules carry one positive charge, which would result in similar charge densities, the configuration of the different QAS molecules within the vesicular membrane might increase the exposure of the positive charge of DDAB compared to CTAB, thus revealing higher ZP. A similar finding was observed by Refai et al ( 2022) [51]. Regarding the effect of increasing the CHO molar ratio (X 2 ) on the ZP values of the quatsomal formulae, it was found that the ZP values increased by increasing the CHO molar ratio; these results might be due to the negative effect of CHO molar ratio on quatsomes PS where increasing CHO molar ratio led to a significant reduction in quatsomes PS which led to increasing surface ratio and subsequently increased ZP values.…”
Section: Effect Of Formulation Variables On Zeta Potentialsupporting
confidence: 91%
“…Although both QAS molecules carry one positive charge, which would result in similar charge densities, the configuration of the different QAS molecules within the vesicular membrane might increase the exposure of the positive charge of DDAB compared to CTAB, thus revealing higher ZP. A similar finding was observed by Refai et al ( 2022) [51]. Regarding the effect of increasing the CHO molar ratio (X 2 ) on the ZP values of the quatsomal formulae, it was found that the ZP values increased by increasing the CHO molar ratio; these results might be due to the negative effect of CHO molar ratio on quatsomes PS where increasing CHO molar ratio led to a significant reduction in quatsomes PS which led to increasing surface ratio and subsequently increased ZP values.…”
Section: Effect Of Formulation Variables On Zeta Potentialsupporting
confidence: 91%
“…Using Bruker FTIR (Shimadzu, Japan) and Attenuated Total Reflectance (ATR) technology, the samples were examined. Utilizing FTIR spectral scanning between 400 cm-1 and 4000 cm-1 (19)(20)(21)(22) .…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%